The technique of plasma gelation - Colichón A., Héctor (1964)
1. The plasma is gelled by the action of the broth "ML" , prepared from peptic digestion of milk and pork bellies . Two . Factors that time , amount of citrate or citrate plasma , influence the phenomenon of gelation . Three . Also the species and individual and pathological factors can influence the Gelation of Plasma. April . That Streptococcus pyogenes , group A, human Gel liquefacta quickly and complete. Rabbit Gel liquefaction resists . May . That the Micrococcus pyogenes and Enterococcus ( Group D ) Gel slowly liquefactan partially or tubular shape ; Having strains or types that make full and quickly. 6. Pseudomonas aeruginosa that liquefactan Gel . 7. Bacillus anthracis liquefactan the gel and produce arborescences and gelatin, these being closely related to such colonial variation. 8. Staphylococci strains that are fast and complete rabbit gel are not as active for human Gel liquefaction . ( Table 8 B).